The Use of Taboo in Djenar Maesa Ayu’s Mereka bilang, saya monyet! - Nurhantoro, Tri Septa (Journal of Language and Literature, 2014)
This paper concerns on the use of taboo expressions in a literary work: Djenar’s Mereka Bilang Saya Monyet!, which is about eighty. Based on those data, those expressions can be grouped into their categories and degrees of politeness-impoliteness. Those categories are: comparison with animal, bodily effluvia, bodily organ, mental defect, disease, torturing-rapingkilling, sexual activity, sexual-related behavior, consumption, place and verbal insult. Meanwhile, the degrees of politeness-impoliteness are: euphemism, orthophemism and dysphemism. It is expected that the reader of this paper can comprehend the use of taboo, particularly in a literary work. Keywords: taboo, politeness, impoliteness